KARAKTERISTIK RAGAM KULTIVAR KELAPA (Cocos nucifera L.) YANG DIGUNAKAN SEBAGAI BAHAN UPAKARA PADUDUSAN ALIT DI BALI - Eniek Kriswiyanti (BERITA BIOLOGI, 2012)
Exploration have been conducted to determine characters variation of coconut (Cocos nucifera L.) usually used in Upakara Padudusan Alit ceremonial by Balinese people, covering coconut plantation areas in each regency (kabupaten) of Bali.The characterization is based on measurement and observation of parts of plant according to ”Descriptors for Coconut” (IBPGR, 1992). Upakara Padudusan Alit use five “cultivars” of coconut known as "nyuh panca warna", derived from coconut with specific individual character i.e. has bole. There are five cultivars C. nucifera L. var. typica Nar. ), i.e. ‘Gading Tall', 'Bulan Tall', 'Udang Tall' and 'Sudamala Tall'. Besides there are 4 derived cultivars from Dwarf coconut (Cocos nucifera L. var. Riff nana), i.e. ‘Gadang Dwarf, 'Gading Dwarf ', 'Bulan Dwarf ' and ‘Udang Dwarf'. Characteristics of each coconut are in certain part, like Gadang, Gading, Bulan, with green, yellow and white epicarp. The Nyuh Udang is red in calyx base or in mesocarp; inflorescence of ‘Sudamala tall’ has two bracts, branched spatha and flat spikelet stalk. Determination key of these cultivars is produced.